Teacher Motivation In The Development Of Electronic Teaching Materials In The Yunior High School 7 Of Bengkulu City - Connie, Connie; Risdianto, Eko; Zuki, Meizul (EARR (Educational Administration Research and Review), 2021)
This study aims to analyze the motivation of teachers in the development of electronic teaching materials in JuniorHigh Schools 7 in Bengkulu City. This research is a mix method research (quantitative and qualitative). The researchsample consisted of 20 teachers in Junior High School 7 in Bengkulu City. The technique used is the samplingtechnique (side purposive). The research instrument used a Likert scale questionnaire with 20 question items. Fromthis data, the results show that the items used to collect data in this study are valid with a validity of 3.265 and reliablewith a reliability of 0.91. The average of all items answered agreed by the respondent. So it can be concluded thattraining activities can foster teacher motivation in developing electronic teaching materials.